2005
DOI: 10.1159/000087271
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Hepatitis C in Southern Taiwan

Abstract: Chronic hepatitis C virus (HCV) infection may lead to cirrhosis and hepatocellular carcinoma. Interferon (IFN)-α is effective in the treatment of chronic hepatitis C. The rate of response to IFN is enhanced by increasing the IFN dose. Extending the treatment duration can reduce the relapse rate. Addition of ribavirin to IFN increases the sustained virological response (SVR). Thus, combination therapy with IFN and ribavirin was adopted for the treatment of chronic hepatitis C in Kaohsiung Medical University Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 78 publications
2
57
0
Order By: Relevance
“…This indicates that AD could, to some extent, reduce the effect of these cormobidities on cancer development, although further investigation is warranted. In a country such as Taiwan, with high endemic hepatitis B and C virus, hepatitis viruses might have a greater impact on the development of cancer in cirrhosis patients [41,42]. …”
Section: Discussionmentioning
confidence: 99%
“…This indicates that AD could, to some extent, reduce the effect of these cormobidities on cancer development, although further investigation is warranted. In a country such as Taiwan, with high endemic hepatitis B and C virus, hepatitis viruses might have a greater impact on the development of cancer in cirrhosis patients [41,42]. …”
Section: Discussionmentioning
confidence: 99%
“…Taiwan is a hyperendemic country for hepatitis B virus (HBV) infection and some HCV endemic areas have been found with high prevalence of anti-HCV [18][19][20]. The present study aimed to elucidate the association between low platelet count and HCV infection, particularly HCV viremia, in a large scale, community-based population, taking the role of hepatic fibrosis into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Combination therapy with interferon (IFN) plus ribavirin (RBV) has greatly improved the treatment efficacy and is the mainstream of treatment for chronic hepatitis C infection (CHC). [3][4][5][6][7] Nonetheless, it has been shown that once cirrhosis occurs, refractory to anti-viral therapy may follow. Even after eradication of the virus, HCC and ⁄ or liver failure may develop in cirrhotic patients.…”
Section: Introductionmentioning
confidence: 99%